Thermal Performance of Coiled Square Tubes at Large Temperature Differences for Heat Exchanger Application - Kurnia, J.C. (Taylor and Francis Ltd., 2016)
In many heat exchanger applications, working fluid inside the tubes is subjected to considerable temperature changes. Coiled tubes are used widely in heat exchanger applications due to the enhanced heat transfer rate caused by secondary flows. This study examines the thermal performance of three configurations of coiled tubes of square cross-section, namely, in-plane, helical, and conical coiled tubes, subjected to a large temperature difference between the fluid and the wall and compares it with that of a straight tube of identical cross-section area and length. The concept of figure of merit (FoM) is introduced to compare the heat transfer performance of the various configurations tested. The results indicate that FoM increases as the wall temperature is increased. In addition, the combination of temperature-induced buoyant flow and curvature-induced secondary flow significantly affects the flow behavior and heat transfer performance inside the tubes. The coil pitch in helical and conical tubes has an adverse effect on the heat transfer performance due to shift in vortices generation. The in-plane spiral tube operates at a higher wall temperature and lower Reynolds number, which gives rise to a higher FoM. The highest Nusselt number is obtained for the in-plane spiral tube at higher wall temperature and higher Reynolds number, which shows potential for practical applications. Â© 2016, Copyright Â© Taylor and Francis Group, LLC.